O "horror" do cotidiano feminino: um estudo de quatro contos de Amparo Dávila - Freitas, Gabriela Seguesse (Universidade Federal de São Carlos, 2024)
This master's thesis aims to investigate the underlying horror in the daily lives of the female protagonists in four short stories by the Mexican writer Amparo Dávila: “El huésped” (1959), “La señorita Julia” (1959), “El último verano” (1977), and “Tina Reyes” (1961), which highlight the underlying horror in the daily lives of women whose existence was predominantly confined to the domestic and familial sphere in most of the 20th century. The analysis of these short stories reveals the recurrent presence of images and symbols, such as the monster figure, the house depicted as locus horribilis, marital ties as a source of conflict for the protagonists, and the uncanny, characteristics that connect Dávila’s writing to the Female Gothic, a term coined by feminist literary critics in the 1970s to trace a tradition among Gothic works written by women and emphasize the experiences of these authors. Recognition of this tradition is crucial, as many female writers face an “anxiety of authorship,” seeking representation in a literary tradition that often appears absent. Additionally, in Latin American literature, the presence of gothic and horror aesthetics was long denied, possibly due to a reluctance to admit European influence. However, reclaiming and positioning works like those of Dávila in the literary universe can expand the diversity of stories analyzed through these categories. Therefore, this study seeks to examine how these narrative resources expose gender issues in Dávila’s four selected stories and, in doing so, question: What can the anxieties of these protagonists reveal about the daily life of women in the second half of the 20th century?
El "horror" de la vida cotidiana de las mujeres: un estudio de cuatro cuentos de Amparo Dávila
The "horror" of women's daily lives: a study of four short stories by Amparo Dávila
Keywords: Contos; Feminismo; Horror; México; Feminism; Short stories; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS